Real estate developer's product positioning: AHP-utility-based model - Chiang, Ting-Yi (International Journal of Strategic Property Management, 2019)
Inappropriate land development decisions lead to wasted land resources; such bad decisions can negatively impact urban landscapes and the environment, which makes the decision of an appropriate residential environment difficult. Therefore, a suitable assessment model is required to resolve this complexity. The present study applied the fuzzy Delphi method, analytical hierarchy process, utility theory, and other research methods to construct an evaluation model for residential environment location. the study findings reveal that consumers are attracted by regional environmental conditions and architectural design. However, the study found that community welfare is neglected. This model can help decision makers to evaluate utility values and profitability, in order to select the most suitable environment. Therefore, related authorities should strengthen community welfare and neighborhood development. Furthermore, social resources should be integrated in order to deliver social welfare and services to the community, thus enabling people in the community to obtain the necessary resources and assistance.